Accelerated discovery of nanomaterials using computer simulation - Nguyen Dac Trung,; Nguyen Thi Hong Hanh,; Le Duy Minh,; Truong Xuan Hung, (Vietnam Journal of Science and Technology, 2018)
Next-generation nanotechnology demands new materials and devices that are highly efficient, multifunctional, cost-effective and environmental friendly. The need to accelerate the discovery of new materials therefore becomes more pressing than ever. Over the past two decades, self-assembly techniques have provided a promising means for fabricating nanomaterials, where the underlying structures are formed by the self-organization of building blocks, such as nanoparticles, colloids and block copolymers, in a similar fashion to biological systems. The fundamental challenges to these bottom techniques are to design suitable assembling units, to tailor their interaction rules and to identify possible assembly pathways. In this report, we will demonstrate how computer simulation has been a powerful tool for tackling these fundamental challenges, providing not only profound insights into the complex interplay between the building blocks’ geometry and their interactions, but also valuable predictions to inspire on-going and future experiment. Theoretical background of self-assembly studies; simulation methods and data analysis tools commonly used will also be discussed.